Mother-in-Law Reports of Closeness to Daughter-in-Law: The Determinant Triangle with the Son and Husband. Issue 1 (5th November 2018) - Woolley, Michael E; Greif, Geoffrey L
Abstract: For a mother-in-law (MIL) and daughter-in-law (DIL), the benefits of maintaining a close relationship weave through other central family relationships. Those relationship triangles start with one's son, who is the other's husband, and echo through the raising of any grandchildren from the marriage. The current study examined the factors that related to MIL reports of having a close relationship with her DIL. Using survey data gathered from 267 MILs authors report on a regression model that included six factors that predicted closeness. Within the MIL relationship, the MIL reporting that the DIL was helpful and had similar interests to her predicted a close relationship. When the MIL reported being close to her son and the son being happy with the relationship she had with the DIL, this predicted a closer relationship between the MIL and DIL. The MIL feeling left out within the relationship triangle with the son and DIL was associated with less closeness. Closeness was increased when the MIL reported more time spent per month with the DIL. The article concludes with a discussion of research and practice implications.